2019
DOI: 10.1097/crd.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Is Anacetrapib Better Than Its CETP Inhibitor Counterparts?

Abstract: Cholesterol metabolism and transport has been a major focus in cardiovascular disease risk modification over the past several decades. Hydroxymethylglutaryl-CoA reductase inhibitors (statins) have been the most commonly used agents, with the greatest benefit in reducing both the primary and secondary risks of cardiovascular disease. However, heart disease remains the leading cause of death in both men and women in the United States. Further investigation and intervention are required to further reduce the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Three CETP inhibitors, torcetrapib, dalcetrapib and evacetrpib, when tested in humans, which either increased cardiovascular risk or were neutral, while a fourth, anacetrapib, showed modest cardiovascular benefit [ 205 , 206 , 207 , 208 ]. Of these drugs, only anacetrapib, in the phase 3 randomized, placebo-controlled REVEAL trial (Randomized Evaluation of the Effects of Anacetrapib through Lipid-Modification), showed a 9% relative risk reduction in major coronary events in persons with pre-existing ASCVD after a median of 4 years of treatment [ 209 , 210 ]. This effect of anacetrapib has been attributed to decreased LDL-C accompanied by a reduction in apoB-containing lipoprotein particles but may also be explained by a decrease in small VLDL particles [ 211 ].…”
Section: Apob As a Target Of Cvd Treatmentmentioning
confidence: 99%
“…Three CETP inhibitors, torcetrapib, dalcetrapib and evacetrpib, when tested in humans, which either increased cardiovascular risk or were neutral, while a fourth, anacetrapib, showed modest cardiovascular benefit [ 205 , 206 , 207 , 208 ]. Of these drugs, only anacetrapib, in the phase 3 randomized, placebo-controlled REVEAL trial (Randomized Evaluation of the Effects of Anacetrapib through Lipid-Modification), showed a 9% relative risk reduction in major coronary events in persons with pre-existing ASCVD after a median of 4 years of treatment [ 209 , 210 ]. This effect of anacetrapib has been attributed to decreased LDL-C accompanied by a reduction in apoB-containing lipoprotein particles but may also be explained by a decrease in small VLDL particles [ 211 ].…”
Section: Apob As a Target Of Cvd Treatmentmentioning
confidence: 99%
“…This focus on raising HDL cholesterol levels has led to the development of CETP inhibitors which block the CETP mediated transfer of cholesterol from HDL to triglyceride rich lipoproteins such as VLDL. These drugs increase HDL cholesterol levels by more than 25% (up to 60%), but largely have not reduced cardiovascular events (107,109,(112)(113)(114)(115)(116)(117)(118). More recent attempts at increasing HDL particle number and/or function have focused on infusion of reconstituted HDL, administration of ApoA1 mimetics, or upregulation of ApoA1 production by liver (119)(120)(121)(122)(123)(124).…”
Section: Hdl Targeted Therapeuticsmentioning
confidence: 99%
“…It has been reported that CETP plays a key role in atherosclerosis through its impact on lipid metabolism [1]. Thus, there have been many efforts to modify the composition of the plasma lipoprotein favorably through inhibition of CETP activity [3].…”
Section: Introductionmentioning
confidence: 99%